USING QUESTIONS AIMED AT CRITICAL THINKING AND PROBLEM-SOLVING IN SCHOOL MATHEMATICS LESSONS - Nuritdinov, Jalolxon; Abdullayeva , E’zozaxon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
In this article, methods for making school mathematics lessons more useful, easier to understand, and more engaging for students are discussed. For this purpose, the questions and tasks used in school mathematics classes to develop students’ critical thinking skills and to form problem-solving abilities for complex problems are classified. Special attention is given to logical numerical questions that require reasoning, analysis, and justification rather than simple calculation. Examples of questions from each group and their solution methods are provided. In addition, the presented types of questions and problems are also categorized according to students’ age groups. At the end of the article, techniques for constructing questions aimed at developing critical thinking and problem-solving skills are also demonstrated.